2008
DOI: 10.3324/haematol.12211
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and genotype report on homozygous and heterozygous patients with congenital factor X deficiency

Abstract: Factor X deficiency is a severe rare hemorrhagic condition inherited as an autosomal recessive trait. It is one of the most severe recessive inherited coagulation disorders. We analyzed the clinical manifestations, laboratory phenotype and genotype in 10 patients with severe Factor X deficiency and in their heterozygous relatives. The most frequent bleeding episodes were hematomas (70%) and gum bleeding (60%). Fifty percent of the homozygous patients required blood transfusion and one-third of heterozygotes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…We also found that the heterozygous individuals with factor X and XIII deficiencies had massive and uncontrolled bleedings during minor operations and minor traumas, respectively. This finding in factor X heterozygous individuals is compatible with a previous study [22]. Heterozygous Bernard-Soulier syndrome individuals also had significantly higher incidence of massive bleeding during delivery and hypermenorrhea.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the heterozygous individuals with factor X and XIII deficiencies had massive and uncontrolled bleedings during minor operations and minor traumas, respectively. This finding in factor X heterozygous individuals is compatible with a previous study [22]. Heterozygous Bernard-Soulier syndrome individuals also had significantly higher incidence of massive bleeding during delivery and hypermenorrhea.…”
Section: Discussionsupporting
confidence: 93%
“…Menorrhagia, spontaneous abortion, and bleeding during vaginal delivery were reported in ;20% of women with all deficiencies. [17][18][19] Women with RBDs require specific attention and care; in addition to the common bleeding symptoms, they may also experience gynecologic bleeding. 20,21 Beyond menorrhagia, affected females are at increased risk of hemorrhagic ovarian cysts, endometriosis, endometrial hyperplasia, polyps, and fibroids.…”
Section: Clinical Symptomsmentioning
confidence: 99%
“… demonstrated three mutations being associated with ICH: Gly380arg, splice site mutation IVS/‐1G>A, and Tyr163delAT; however, Karimi et al. were not able to confirm these findings. Using linear regression analysis, Peyvandi et al.…”
Section: Discussionmentioning
confidence: 66%